2021
DOI: 10.1097/brs.0000000000004199
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surgeon Experience and Subspeciality on the Reliability of the AO Spine Sacral Classification System

Abstract: Study Design. Cross-sectional survey. Objective. To determine the influence of surgeons' level of experience and subspeciality training on the reliability, reproducibility, and accuracy of sacral fracture classification using the Arbeitsgemeinschaft fu ¨r Osteosynthesefragen Spine Sacral Classification System. Summary of Background Data. A surgeons' level of experience or subspecialty may have a significant effect on the reliability and accuracy of sacral classification given various levels of comfort with ima… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…They did not find differences between spine and trauma pelvic surgeons or among surgeons with different levels of experience. Karamian et al [4] obtained better interrater and intrarater agreement using this classification. In this study, 26 patients were evaluated by 172 observers from different specialties and with different levels of expertise.…”
Section: Validationmentioning
confidence: 65%
See 3 more Smart Citations
“…They did not find differences between spine and trauma pelvic surgeons or among surgeons with different levels of experience. Karamian et al [4] obtained better interrater and intrarater agreement using this classification. In this study, 26 patients were evaluated by 172 observers from different specialties and with different levels of expertise.…”
Section: Validationmentioning
confidence: 65%
“…Karamian et al [4] obtained better interrater and intrarater agreement using this classification. In this study, 26 patients were evaluated by 172 observers from different specialties and with different levels of expertise.…”
Section: Validationmentioning
confidence: 76%
See 2 more Smart Citations
“…Even though our results suggest there is no correlation between surgeon experience and improved AO Spine Subaxial Injury Classification System reliability or reproducibility, no study has examined if increased application of the classification to cervical spine injuries improves a participants accuracy. Of note, no previous study has found a correlation between surgeon experience and the reliability and reproducibility of different AO Spine classifications [12,13].…”
Section: Discussionmentioning
confidence: 97%